2011
DOI: 10.1063/1.3560464
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on migration mechanism in SrTiO3

Abstract: The atomistic behavior of migration in SrTiO3 was investigated by first-principles nudged elastic band calculations. Calculated migration energies for Sr and oxygen are consistent with experimental values. In contrast, the calculated energy for Ti with a simple Ti-vacancy mechanism is far larger than the experimental value. In examining different Ti-migration mechanisms, the Ti-migration energy is found to decrease and become comparable to the Sr-migration energy by introducing a Sr vacancy. This Sr-vacancy-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…The most likely combination of Zr 4+ migration involving both site vacancies is shown in path B in Figure 5. Recently, we have shown that the diffusion pathway for Zr 4+ via Ba-vacancies is most likely in BZ [17], and we propose that this diffusion mechanism can also be expected for cubic SZ also supported by previous studies [15,25]. …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The most likely combination of Zr 4+ migration involving both site vacancies is shown in path B in Figure 5. Recently, we have shown that the diffusion pathway for Zr 4+ via Ba-vacancies is most likely in BZ [17], and we propose that this diffusion mechanism can also be expected for cubic SZ also supported by previous studies [15,25]. …”
Section: Discussionsupporting
confidence: 61%
“…Abbreviations: ppolycrystalline; sc-single crystal; c-cubic; b-bulk; gb-grain boundaries. (1) Ho in p BaTiO3 gb [11]; (2) Ho in p BaTiO3 b [11]; (3) Ni in p Ba(Ho,Ti)O3 [10]; (4) Ni in sc BaTiO3 [10]; (5) Ni in p BaTiO3 [10]; (6) Si in MgSiO3 [39]; (7) 49 Ti in sc (La,Sr)TiO3 [25]; (8) Zr in sc BaTiO3 [12]; (9) 141 Pr in LaFeO3 gb [40; (10) 141 Pr in LaCoO3 gb [40]; (11) Co in LaCoO3 gb [41]; (12) Cr in LaMnO3 [42];(13) Mn in LaCoO3 [43]; (14) Co in LaCoO3 b [41]; (15) 141 Pr in LaMnO3 [40]; (16) Co in GdCoO3 [44]; (17) Co in EuCoO3 [44]; (18) Co in SmCoO3 [44]; (19) Co in NdCoO3 [44]; (20) Co in PrCoO3 [44]; (21) 50 Cr in (La,Ca)CrO3 gb [45]; (22) Co in LaCoO3 [44]; (23) Mn in LaMnO3 b [42]; (24) Mn in LaMnO3 gb [42]; (25) Fe in LaFeO3 gb [46]; (26) Fe in LaFeO3 b [46]; (27) 141 Pr in LaCoO3 b [40]; (28) 141 Pr in LaFeO...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even different density functional theory (DFT) calculations exhibit significant deviations between the calculated values of the oxygen vacancy diffusion barrier. The DFT estimations of the energy barrier range from 0.35-0.9 eV 19,20,21,22,23,24,25,26 . The deviations in DFT results are considerable and the underlying cause for such deviations is unclear, as different simulation setups and parameters have been employed in the previous calculations.…”
Section: Introductionmentioning
confidence: 99%
“…4),6), 56) In addition, it was also revealed that the migration of Sr-vacancy is much more difficult than that of oxygen-vacancy. 58) By considering those defect formation and diffusion behaviors in SrTiO 3 , Sr deficient GB was fabricated by a suitable heat treatment. By investigating such GB, it was revealed that the Sr vacancy at the GB plays important role to bring about the non-linear IV characteristics.…”
Section: Anti-bondingmentioning
confidence: 99%